Decent and Sustainable Work: Around the Discussion on the Importance of International Law in the Regulation of Employment Relations - Wrocławska, Tatiana (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Transnational strategies not only show the contemporary risks in the world of work, but also point to directions and measures to mitigate them. In this regard, recognising a certain regression in the protection of workers’ rights, it is worth emphasising the question of the role of decent and sustainable work, which occurs in one of the important documents of the International Labour Organisation (hereafter: the ILO). It is noteworthy that the adjective ‘sustainable’ increasingly appears in various social, economic, and environmental aspects, including but not limited to sustainable employment, the workplace, and sustainable work. This raises the question about the meaning of the phrase ‘decent and sustainable work’. Apart from a rather general link to certain areas of the strategic objectives, we do not find an answer to it in the documents in which it appears. For this reason, in the presented study it was decided to characterise briefly both concepts considering the achievements of the ILO and Eurofund as well as the relationship occurring between them. Moreover, an attempt was made to give an answer on the starting point for effectively counteracting negative phenomena and related risks in the world of work within the framework of the concept of decent work.